Effect of cumin and cinnamon on lipid profile in middle-aged women with dyslipidemia: a double blind, randomized controlled clinical trial - Pishdad, Samaneh; Nadjarzadeh, Azadeh; Salehi Abargouei, Amin; Karimi Nazari, Elham; Papoli, Maryam (Progress in Nutrition, 2018)
Abstract: Hyperlipidemia is a risk factor for the cardiovascular disease. The aim of the present study is to compare the effect of cumin and cinnamon on lipid profile in middle aged women with dyslipidemia. Materials & methods: In this randomized clinical trial, 99 women with dyslipidemia were randomly assigned to consume 3 g/d cumin or cinnamon in the form of 6 capsules or placebo three times per day for 8 weeks. Dietary intake and physical activity were determined before and after the study. Quantitative data were compared using ANCOVA with adjusting dietary intake and physical activity. Demographic factors were compared using chi-square test. All statistical analyzes were at a significance level of 95%. Results: All variables had a normal distribution except LDL. Cumin and cinnamon reduced serum levels of total cholesterol ,triglyceride and also serum HDL-cholesterol levels (11). This study indicated that there were not any significant differences among three groups in terms of the amount of LDL and TG (p>0.05). Also there was no difference concerning the amount of HDL (p>0.05). However, total cholesterol in cumin and cinnamon significantly decreased after 8 weeks (p=0.004). Mean changes in the cholesterol concentrations in cumin and cinnamon groups were -31, -19 mg/dl. Conclusion: This study provided evidence that show using cumin and cinnamon have effect on reducing serum cholesterol levels , but more research is required.